Leap before you look Black Mountain College : 1933-1957 - Molesworth, Helen 1966-; Erickson, Ruth (Institute of Contemporary Art, 2015)
In 1933, John Rice founded Black Mountain College in North Carolina as an experiment in making the arts central to learning. Though it operated for only twenty-four years, this pioneering school played a significant role in fostering avant-garde art, music, dance, and poetry, and an astonishing number of important artists taught or studied there. Among the instructors were Josef and Anni Albers, John Cage, Merce Cunningham, R. Buckminster Fuller, Karen Karnes, Willem de Kooning, and M.C. Richards, and students included Ruth Asawa, John Chamberlain, Ray Johnson, Robert Rauschenberg, and Cy Twombly. Leap Before You Look is a singular exploration of this legendary school and the work of the artists who spent time there. Scholars from a variety of fields contribute original essays about diverse aspects of the college--spanning everything from the college's farm program to the influence of the Bauhaus--and about the people and ideas that gave it such a lasting impact. Catalogue entries highlight selected works, including writings, musical compositions, visual arts, pottery, and weaving. The book's fresh approach and rich illustrations convey the atmosphere of creativity and experimentation unique to Black Mountain College that served as an inspiration to so many. This timely volume will be essential reading for anyone interested in art, radical pedagogy, and the enduring legacy of the college. -- Front jacket flap